2016
DOI: 10.1007/s00705-016-2958-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and toxicity evaluation of sesbania mosaic virus nanoparticles in mice

Abstract: Sesbania mosaic virus (SeMV), a 30-nm spherical plant sobemovirus, is suitable for developing functionalized nanoparticles for biomedical applications. However, the in vivo behavior of SeMV and the clinical impact following its delivery via the oral or intravenous route are not known. To address this question, we examined the biodistribution, toxicity and histopathological changes in SeMV treated mice. No toxic effects were observed in mice administered high doses (100 mg and 200 mg per kg body weight orally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The clearance kinetics of proteins and VLPs have been reported in several studies [3] , [57] , [58] , [59] . In general, particulate materials including viral proteins are removed from the blood circulation relatively quickly by the reticulo-endothelial system (RES) (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The clearance kinetics of proteins and VLPs have been reported in several studies [3] , [57] , [58] , [59] . In general, particulate materials including viral proteins are removed from the blood circulation relatively quickly by the reticulo-endothelial system (RES) (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that a recombinant ancestral uricase packaged in Qβ nanoparticles and orally delivered to uricase-knockout mice is able to prevent the buildup of endogenous uric acid levels and suppress some of the renal damage caused by hyperuricemia during a limited treatment regime. The use of virus-like particles as oral vaccine candidates is well known, and a few accounts have described or inferred remarkable stability of different VLPs toward the degradation in the GI tract While we have not directly analyzed the fate of Qβ VLPs after oral delivery, the retention of significant uricase activity, presumably in the intestine, suggests that this particle also resists digestive enzymes and acidic hydrolysis, and imparts hydrolytic stability to the packaged enzyme as well.…”
Section: Resultsmentioning
confidence: 97%
“…Large quantities of these viruses readily accumulate in plants, and the extraction and purification of plant viruses is efficient (and economically feasible in terms of time and materials). Moreover, many plant viruses are stable, particularly under physiological conditions, so that strict adherence to the vaccine chain is not required for storage and transfer [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%